Preparation of domoic acid analogues using a bioconversion system, and their toxicity in mice. Issue 36 (1st September 2021) - Maeno, Yukari; Kotaki, Yuichi; Terada, Ryuta; Hidaka, Masafumi; Cho, Yuko; Konoki, Keiichi; Yotsu-Yamashita, Mari
Abstract : Domoic acid analogues were prepared by chemical synthesis and enzymatic stereoselective cyclization using a bioconversion system. The 7'-carbonyl group in the terminus of the side chain was suggested to be crucial for the toxicity in mice. Abstract : Domoic acid (1, DA), a member of the natural kainoid family, is a potent agonist of ionotropic glutamate receptors in the central nervous system. The chemical synthesis of DA and its derivatives requires considerable effort to establish a pyrrolidine ring containing three contiguous stereocenters. Recently, a biosynthetic cyclase for DA, DabC, was identified. This enzyme cyclizes the linear precursor of isodomoic acid A (IA) to IA, a bioactive DA analogue. In this study, we developed a bioconversion system to obtain DA analogues from linear substrates prepared by simple chemical synthesis using DabC expressed in Escherichia coli, in vivo . Three IA analogues with various substitutions at the C7′-geranyl terminus were prepared using this system: two minor natural analogues, 7′-methyl-IA (5 ) and 7′-hydroxy-IA (6 ), and one new unnatural analogue, 7′-amide-IA (7 ). In addition, the toxicity of these DA analogues in mice was examined by intracerebroventricular injection. Most of the mice injected with 5 (3 nmol) and 6 (3 nmol) did not show any adverse symptoms, whereas the mice injected with 7 (3 nmol) showed typical symptoms induced by DA (1, 0.7 nmol) and IA (2, 3 nmol). These results suggest that the 7′-carbonyl group in the side chain of IA (2 ) is crucial for its toxicity. The docking studies of DA, IA (2 ), 5, 6, and 7 to GluK1 supported these results.